The Effectiveness of Reality Therapy and Emotion-Focused Therapy on Cognitive Avoidance in Women with Marital Distress - Maryam Toope; Seyed Mahmood Mirzamani Bafghi; Mohammad Hatami (Iranian Journal of Educational Research)
Objective: The objective of the present investigation was to assess the efficacy of reality therapy and emotion-focused therapy in mitigating cognitive avoidance among women experiencing marital distress. Methods: This research was conducted as a quasi-experimental pre-test-post-test design incorporating a control cohort and an interval for follow-up assessments. The studied population comprised all married women encountering marital distress who sought assistance at counseling clinics located in the second district of Tehran during the summer of 2023. A sample of 45 participants was selected through convenience sampling and being randomly allocated into three distinct groups: Experiment 1 involving Reality Therapy (n=15), Experiment 2 encompassing Emotion-Focused Therapy (n=15), and a control group (n=15). For the acquisition of research data, the study utilized the cognitive avoidance questionnaire developed by Sexton and Dugas (2009) and marital distress questionnaire formulated by Weissman, Snyder, and Bach (2009). Results: The findings indicated that the average cognitive avoidance scores for the groups receiving reality therapy and emotion-focused therapy were significantly reduced compared to those recorded in the control group (p<0.05). Furthermore, the average cognitive avoidance score within the emotion-focused therapy group was significantly lower than that of the reality therapy group (p<0.05). Conclusions: The results substantiate the efficacy of psychological interventions in diminishing cognitive avoidance and indicate that emotion-focused therapy may serve as a more efficacious intervention.